Integration of Eco Design in Supply Chain Management - Obrecht, Matevž (Mastering Sustainability in Supply Chains, 2026)
Due to the increasing population, increasing standard of living, and consequently, increasing human activities and production, environmental concerns are gaining more and more importance. It is becoming clear that our planet can no longer regenerate, and resources are being used in an unsustainable manner. Environmentally conscious and more sustainable practices provide organizations with a competitive advantage and the ability to operate in the long term. However, focusing on the environmental aspect within company walls, in just one part of the supply chain, is not sufficient for effective improvements. Environmental impacts occur throughout the entire supply chain, from resource extraction, material and component production, final product manufacturing, distribution, usage, to the end of the product's life cycle. Eco-design, as a tool for creating environmentally-friendly products, compels companies to consider various environmental impacts that occur beyond company walls and work towards preventing and minimizing them already within product/service planning and design phase.